PENGARUH CITRA MEREK, PERSEPSI HARGA, LABEL HALAL, DAN KESADARAN MEREK TERHADAP KEPUASAN KONSUMEN (STUDI PADA KONSUMEN MI SAMYANG DI KUDUS) - Audika, Niken Chika Aisya; Arumsari, Nurul Rizka (Bisnis-Net, 2025)
This study aims to testing and analyzing the impact of brand image, price perception, halal label, and brand awareness on the level of consumer satisfaction of Samyang in Kudus. This study involved 115 respondents who were users of Samyang products. Data collection was carried out through questionnaires, and data analysis was carried out using SmartPLS software version 4. The tests carried out include descriptive statistical analysis, measurement tests (outer model), convergent validity, discriminant validity, composite reliability, structural model tests (inner model), and hypothesis testing. The results of the study indicate that: 1) brand image has a positive and significant effect on consumer satisfaction of Samyang in Kudus 2) price perception has a positive and significant effect on consumer satisfaction of Samyang in Kudus 3) halal label has a positive and significant effect on consumer satisfaction of Samyang in Kudus 4) brand awareness has a positive and significant effect on consumer satisfaction of Samyang in Kudus.